Activation of co-pyrolysis chars from rice wastes to improve the removal of Cr3+ from simulated and real industrial wastewaters. (10th September 2020) - Dias, Diogo; Bernardo, Maria; Matos, Inês; Fonseca, Isabel; Pinto, Filomena; Lapa, Nuno
Abstract: Chromium is one of the most important raw materials for the European Union. Adsorption has become an important process for the recovery of metals from wastewaters, which has led to a demand for low-cost and eco-friendly adsorbents. The objective of this work was to use new and renewable carbon-based adsorbents from rice wastes in the removal/recovery of Cr(III) from synthetic and real wastewaters. Rice wastes were submitted to co-pyrolysis and the resulting char was optimized through physical and/or chemical activations/treatments. A commercial activated carbon was used for comparison purposes. All adsorbents were characterized (including an ecotoxicity test for the char precursor) and submitted to Cr(III) removal assays from a synthetic solution, in which two solid/liquid ratios (S/L) were tested (5 and 10 g/L). The CO2 activated carbon at a S/L = 5 g/L was the biomass-derived adsorbent that performed better, obtaining a maximum Cr(III) uptake capacity of 9.23 mg/g comparable to the one obtained by the commercial adsorbent at the same S/L (9.80 mg/g). The good results on this biomass-derived carbon were due to the effective volatile matter removal during the activation (from 22.7 to 4.25% w/w), which increased both surface area (from <5.0 to 325 m 2 /g) and ash content (from 30.0 to 40.4% w/w), allowing an increase in Cr(III) removal due to ion exchange mechanism and porosity development. The best adsorbent, under optimized conditions, was also applied to a chromium rich industrial wastewater. The results obtained in this real case application demonstrated a competition effect due to the presence of other ions. Graphical abstract: Image 1 Highlights: Pyrolysis rice waste char was optimized through different activations/treatments. The activated carbons (AC) were characterized and used in Cr(III) removal assays. Physical activation without washing originated the best pyrolysis AC (P1C+PA). P1C+PA presented similar Cr(III) uptake capacities than a commercial AC. P1C+PA performed better in an industrial wastewater than in a synthetic solution.